Land Classes in Sundargarh District, Orissa State and their Genesis, Soil Properties and Land Capability Classes - Biswas, R.R (Journal of Soil and Water Conservation, 2022)
The uncultivated lands include (1) grass or pasture lands and (2) village forests, both situated in uplands and (3) reserve forests, located on hills and hill slopes in high lands of the watershed.In this paper an attempt has been made to show the different characteristics of the soils and the lands in the various land classes described above and to find some correlations between these soil characteristics and the productivity of the land.